2016
DOI: 10.1128/aem.04054-15
|View full text |Cite
|
Sign up to set email alerts
|

SaxA-Mediated Isothiocyanate Metabolism in Phytopathogenic Pectobacteria

Abstract: Pectobacteria are devastating plant pathogens that infect a large variety of crops, including members of the family Brassicaceae. To infect cabbage crops, these plant pathogens need to overcome the plant's antibacterial defense mechanisms, where isothiocyanates are liberated by hydrolysis of glucosinolates. Here, we found that a Pectobacterium isolate from the gut of cabbage root fly larvae was particularly resistant to isothiocyanate and even seemed to benefit from the abundant Brassica root metabolite 2-phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 56 publications
1
44
1
Order By: Relevance
“…; Welte et al . ). This would allow this species to feed on plant organs with high levels of 2PE‐GSL and other ITC forming GSLs.…”
Section: Discussionmentioning
confidence: 97%
“…; Welte et al . ). This would allow this species to feed on plant organs with high levels of 2PE‐GSL and other ITC forming GSLs.…”
Section: Discussionmentioning
confidence: 97%
“…Biotic OCS production from cryptogamic covers is a possibility: In bacteria, novel enzymatic pathways 10 have been described that degrade thiocyanate and isothiocyanate and render OCS as a byproduct (Bezsudnova et al, 2007;Hussain et al, 2013;Katayama et al, 1992;Welte et al, 2016). Evidence for OCS emissions following SCN -degradation has been observed from a range of environmental samples from aquatic and terrestrial origins, indicating a wide distribution of OCS-emitting microorganisms in nature (Yamasaki et al, 2002).…”
Section: Other Terrestrial Ocs Flux Components 20mentioning
confidence: 99%
“…Hydrolysis of isothiocyanate, another breakdown product of 15 glucosinolates (Hanschen et al, 2014), by the SaxA protein also yields OCS, as shown in phytopathogenic Pectobacterium sp. (Welte et al, 2016). Some Actinomycetales bacteria and Mucoromycotina fungi, both commonly found in soils, are also known to emit OCS, but the origin and pathway remains to be elucidated (Masaki et al, 2016;Ogawa et al, 2016).…”
Section: Other Terrestrial Ocs Flux Components 20mentioning
confidence: 99%
“…Brassicales plants employ the GSN–myrosinase defence system which, on tissue damage, releases a blend of toxic volatiles, of which ITCs are particularly toxic to insects and bacteria (Wittstock et al ., ; Dufour et al ., ). We have shown previously that the bacterial saxA gene encodes a hydrolase that can detoxify ITCs in vitro and that the gene is widespread among Enterobacterales (Welte et al ., ; van den Bosch et al ., ). In this study, we demonstrated that deletion of two different saxA gene variants results in greatly reduced virulence of Pectobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…These observations may be the effect of convergent evolution, although differential effectiveness against particular variations of GSN/ITC profiles of hosts cannot be excluded. The presence of two saxA genes in the genome of P. polaris NCPPB3395 and the presence of three saxA genes with unique origins in strains of P. wasabiae (Welte et al ., ) suggest that there may be added benefit to diversifying genomic saxA gene content when infecting specific hosts. The analysis of the distribution of saxA genes in the Pectobacterium genus showed that most Pectobacterium strains isolated from a Brassica host contain one or more saxA genes in their genome, with the exception of one group of P. odoriferum strains (S6, S6–2, and BCS7).…”
Section: Discussionmentioning
confidence: 99%